15-5ph stainless steel and additive manufacturing method and application thereof
The preparation of 15-5PH stainless steel with a heterogeneous layered structure by laser powder bed melting technology solves the problems of insufficient strength and strength-toughness inversion in traditional casting, achieving a balance between high strength and toughness, and is suitable for aero-engines and aircraft structural components.
Patent Information
- Application Number
- CN202410157152.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-02-04
AI Technical Summary
Traditional casting technology cannot meet the high strength requirements of 15-5PH stainless steel, and traditional strengthening methods sacrifice toughness, resulting in a prominent inverse relationship between strength and toughness, making it difficult to process complex workpieces.
15-5PH stainless steel was prepared using laser powder bed melting technology to form a heterogeneous layered structure with alternating fine and coarse grain layers. By controlling the ratio of FCC austenite to BCC martensite and combining specific laser powder bed melting process parameters, a material with both high strength and toughness was prepared.
It achieves a balance between high strength and toughness in 15-5PH stainless steel, making it suitable for reinforcement and repair of aero-engine systems and aircraft structural components.
Smart Images

Figure CN117961088B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal materials technology, and more specifically, to a 15-5PH stainless steel and its additive manufacturing method and application. Background Technology
[0002] 15-5PH martensitic stainless steel possesses excellent strength, ductility, and corrosion resistance, making it widely used in marine, chemical, and aerospace industries. However, conventional casting techniques cannot meet the higher strength requirements of 15-5PH stainless steel, necessitating subsequent forging to improve its mechanical properties. However, machining high-hardness forged sheets into complex workpieces is challenging, severely limiting practical applications. Additive manufacturing technologies, such as laser powder bed fusion (L-PBF), are among the latest rapid prototyping methods, characterized by high energy density, a small heat-affected zone, and cooling rates reaching 1000°C. 3 ~10 8 K / s helps to obtain fine grains, which creates new possibilities for the efficient manufacture of 15-5PH parts with new geometries and excellent performance.
[0003] Strength and toughness are the two most critical mechanical properties of metallic materials, determining their performance in engineering applications. Therefore, achieving a balance between strength and toughness is a crucial theme in the design of engineering structural materials. Traditional methods such as deformation strengthening, solid solution strengthening, precipitation strengthening, and phase transformation strengthening can improve material strength to some extent, but at the expense of toughness, exhibiting a clear strength-toughness inversion relationship. Moreover, the higher the strength of the material, the more pronounced this inversion becomes.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The purpose of this invention is to provide a 15-5PH stainless steel and its additive manufacturing method and application, so as to solve or improve the above-mentioned technical problems.
[0006] This application can be implemented as follows:
[0007] In one aspect, this application provides a 15-5PH stainless steel having a heterogeneous layered structure in its microstructure;
[0008] The heterogeneous layered structure is composed of alternating fine-grained and coarse-grained layers;
[0009] Both the fine-grained layer and the coarse-grained layer contain BCC martensite and FCC austenite, with the content of FCC austenite in the fine-grained layer being higher than that in the coarse-grained layer.
[0010] In an optional embodiment, the average grain size in the fine-grained layer is 1 to 2 μm.
[0011] In an optional embodiment, the FCC austenite content in the fine-grained layer is 9-12% by volume, with the balance being BCC martensite.
[0012] In an optional embodiment, the average grain size in the coarse-grained layer is 3–6 μm.
[0013] In an optional embodiment, the coarse-grained layer contains 4-6% FCC austenite by volume percentage, with the remainder being BCC martensite.
[0014] In an optional embodiment, the 15-5PH stainless steel has a tensile strength of 1122–1161 MPa, a yield strength of 742–825 MPa, an elongation after fracture of 16.0–17.5%, and an impact toughness of 103.0–122.5 J / cm². 2 .
[0015] Secondly, this application provides an additive manufacturing method for 15-5PH stainless steel as described in any of the foregoing embodiments, comprising the following steps: additive manufacturing of 15-5PH stainless steel powder by means of laser powder bed melting.
[0016] In an optional embodiment, the 15-5PH stainless steel powder is a spherical powder with a particle size of 15-53 μm.
[0017] In an optional embodiment, the process parameters for laser powder bed melting include: laser power of 260-300W, scanning speed of 1200-1500mm / s, scanning spacing of 0.06-0.08mm, and powder bed thickness of 0.03-0.05mm.
[0018] Thirdly, this application provides the application of 15-5PH stainless steel as described in any of the foregoing embodiments in aero-engine systems or aircraft structural components.
[0019] The beneficial effects of this application include:
[0020] This application achieves excellent strengthening and toughening effects by preparing a specific heterogeneous layered structure. Furthermore, by controlling the grain size of the fine and coarse grain layers and the ratio of FCC austenite to BCC martensite within a specific range, the 15-5PH stainless steel can simultaneously possess better strength and toughness. This 15-5PH stainless steel can be obtained through additive manufacturing using a specific laser powder bed melting method. It is suitable for strengthening and repairing components in aero-engine systems and aircraft structural parts, such as high-pressure compressor discs and aviation fuel and hydraulic control systems. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a scanning electron microscope image of the heterogeneous layered structure in 15-5PH stainless steel prepared in Example 1 of the present invention;
[0023] Figure 2 This is a backscattered electron diffraction pattern of the heterogeneous layered structure in 15-5PH stainless steel prepared in Example 1 of the present invention.
[0024] Figure 3 This is the backscattered electron diffraction pattern of the fine grains in the heterogeneous layered structure of the 15-5PH stainless steel prepared in Example 1 of the present invention.
[0025] Figure 4 This is a backscattered electron diffraction pattern of the fine-grained FCC austenite and BCC martensite layers in the heterogeneous layered structure of 15-5PH stainless steel prepared in Example 1 of the present invention.
[0026] Figure 5 This is the backscattered electron diffraction pattern of coarse-grained grains in the heterogeneous layered structure of 15-5PH stainless steel prepared in Example 1 of the present invention.
[0027] Figure 6 This is a backscattered electron diffraction pattern of the coarse-grained FCC austenite and BCC martensite layers in the heterogeneous layered structure of 15-5PH stainless steel prepared in Example 1 of the present invention.
[0028] Figure 7 The X-ray diffraction pattern of the 15-5PH stainless steel obtained in Example 1 of this invention is shown in the printed state.
[0029] Figure 8 The printed room temperature tensile stress-strain curves of 15-5PH stainless steel prepared in Example 1 and Comparative Example 1 of this invention are shown.
[0030] Figure 9 This is a scanning electron microscope image of the room temperature tensile fracture surface of 15-5PH stainless steel prepared in the printed state according to Example 1 of the present invention.
[0031] Figure 10 This is a scanning electron microscope image of the room temperature impact fracture surface of 15-5PH stainless steel prepared in the printed state according to Example 1 of the present invention.
[0032] Figure 11This is a scanning electron microscope image of the 15-5PH stainless steel without heterogeneous layered structure prepared in Comparative Example 1 of the present invention.
[0033] Figure 12 This is a scanning electron microscope image of the room temperature tensile fracture surface of the 15-5PH stainless steel prepared in Comparative Example 1 of the present invention.
[0034] Figure 13 This is a scanning electron microscope image of the room temperature impact fracture surface of the 15-5PH stainless steel prepared in Comparative Example 1 of this invention. Detailed Implementation
[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0036] The following provides a detailed description of the 15-5PH stainless steel, its additive manufacturing method, and its application provided in this application.
[0037] This application proposes a 15-5PH stainless steel with a heterogeneous layered structure in its microstructure. Compared with traditional homogeneous structural materials, the heterogeneous material exhibits non-uniform distribution in its internal spatial structure, strength, and even composition.
[0038] In this application, the heterogeneous layered structure is composed of alternating fine-grained and coarse-grained layers. The average grain size of the fine-grained layers is smaller than that of the coarse-grained layers.
[0039] Both the fine-grained and coarse-grained layers contain BCC martensite and FCC austenite, but the content of FCC austenite in the fine-grained layer is higher than that in the coarse-grained layer.
[0040] For reference, the average grain size in the fine-grained layer can be 1 to 2 μm, such as 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or 2 μm, or any other value in the range of 1 to 2 μm.
[0041] The average grain size in the coarse-grained layer can be 3 to 6 μm, such as 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm, or any other value in the range of 3 to 6 μm.
[0042] In this application, the proportion of FCC austenite in the fine-grained layer is 9-12% by volume, with the balance being BCC martensite. Exemplarily, the content of FCC austenite in the fine-grained layer can be 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, or 12%, or any other value within the range of 9-12%.
[0043] Similarly, by volume percentage, the FCC austenite content in the coarse-grained layer is 4-6%, with the balance being BCC martensite. For example, the FCC austenite content in the coarse-grained layer can be 4%, 4.5%, 5%, 5.5%, or 6%, or any other value within the range of 4-6%.
[0044] In some embodiments, the 15-5PH stainless steel provided in this application has a tensile strength of 1122–1161 MPa, a yield strength of 742–825 MPa, an elongation after fracture of 16.0–17.5%, and an impact toughness of 103.0–122.5 J / cm². 2 .
[0045] Continuing from the above, this application, by preparing a specific heterogeneous layered structure, controls the grain size of the fine and coarse grain layers and the ratio of FCC austenite to BCC martensite within a specific range, enabling 15-5PH stainless steel to possess both superior strength and toughness.
[0046] Accordingly, this application also provides an additive manufacturing method for the above-mentioned 15-5PH stainless steel, comprising the following steps: additive manufacturing of 15-5PH stainless steel powder by means of laser powder bed melting.
[0047] The 15-5PH stainless steel powder is a spherical powder with a particle size of 15–53 μm. This powder is readily available for purchase.
[0048] It should be emphasized that the inventors have successfully prepared 15-5PH stainless steel with the best match between strength and toughness by creatively adopting specific laser powder bed melting process parameters.
[0049] In this application, the process parameters for laser powder bed melting include: laser power of 260-300W, scanning speed of 1200-1500mm / s, scanning spacing of 0.06-0.08mm, and powder thickness of 0.03-0.05mm.
[0050] For reference, the laser power can be 260W, 265W, 270W, 275W, 280W, 285W, 290W, 295W or 300W, or any other value in the range of 260 to 300W.
[0051] If the laser power is too low, it is not conducive to high-density forming and is prone to defects such as fusion, porosity, and air bubbles, which deteriorates the performance. If the laser power is too high, it is not conducive to forming and is prone to warping and deformation. At the same time, excessive energy input causes the remelting area to expand, and only uniform fine grain characteristics can be obtained, but heterogeneous layered structures cannot be obtained.
[0052] The scanning speed can be 1200mm / s, 1250mm / s, 1300mm / s, 1350mm / s, 1400mm / s, 1450mm / s or 1500mm / s, or any other value in the range of 1200 to 1500mm / s.
[0053] If the scanning speed is too slow, it will be detrimental to the forming efficiency; if the scanning speed is too fast, it will be detrimental to high-density forming and will easily lead to defects such as fusion, porosity, and air bubbles, which will deteriorate the performance. At the same time, too low energy input can only obtain uniform large grain features, but cannot obtain heterogeneous layered structures.
[0054] The scanning interval can be 0.06mm, 0.065mm, 0.07mm, 0.075mm or 0.08mm, or any other value in the range of 0.06 to 0.08mm.
[0055] If the scanning spacing is too small, it will be detrimental to the forming efficiency; if the scanning spacing is too large, it will be detrimental to high-density forming and will easily lead to defects such as fusion, porosity, and air bubbles, which will deteriorate the performance. At the same time, too low energy input can only obtain uniform large grain features, but cannot obtain heterogeneous layered structures.
[0056] The powder coating thickness can be 0.03mm, 0.04mm, or 0.05mm, or any other value within the range of 0.03 to 0.05mm.
[0057] If the powder layer is too thin, it will hinder the powder layering process; if the powder layer is too thick, it will hinder high-density forming and may result in incomplete firing, thus deteriorating the performance.
[0058] Continuing from the above, this application successfully prepared 15-5PH stainless steel that satisfies the above-mentioned specific heterogeneous layered structure (including specific grain size and the ratio of FCC austenite to BCC martensite) by coordinating the laser power, scanning speed, scanning spacing and powder thickness within a specific range, so that the obtained 15-5PH stainless steel has both superior strength and toughness.
[0059] It should be noted that the proportion of FCC austenite in the fine-grained layer is relatively higher than that in the coarse-grained layer. This is because the laser powder bed melting process has a layer-by-layer deposition characteristic during rapid cooling. Each deposition (N+1) introduces heat back into the already solidified deposited layer (N), causing the solidified layer to receive additional heat and resulting in the reversion of martensite to austenite. Therefore, this application obtains a heterogeneous layered structure by using appropriate laser powder bed melting process parameters, and by controlling the grain size of the fine and coarse-grained layers and the ratio of FCC austenite to BCC martensite in the heterogeneous layered structure, high-strength and high-toughness 15-5PH stainless steel is prepared.
[0060] The aforementioned heterogeneous deformation strengthening (back stress strengthening) mechanism is mainly manifested in the following aspects: During the plastic deformation process of heterogeneous materials, the mechanical incompatibility between the soft and hard regions leads to significant non-uniform deformation, exhibiting a significant Bauschinger effect. Back stress consists of two parts: 1) residual stress caused by non-uniform deformation of the heterogeneous regions during loading and unloading, i.e., intergranular back stress; 2) non-uniform deformation between the soft and hard regions also induces a large strain gradient during plastic deformation, accumulating a large number of geometrically necessary dislocations at the heterogeneous interface, thus generating intragranular back stress, i.e., kinematic or back stress strengthening. Therefore, regardless of whether it is intergranular back stress or intragranular back stress, its physical origin is due to the non-uniform deformation of the material's non-uniform microstructure, such as orientation mismatch, grain size differences, and inclusions.
[0061] Intergranular back stress is an inevitable product of residual stress during the loading and unloading process of heterogeneous materials, while back stress strengthening (intragranular back stress) is induced by the complex dislocation activity within the heterogeneous material. Therefore, the latter directly controls the additional work hardening behavior of heterogeneous materials. Back stress strengthening gradually increases with the yield strength of the material, and gradient structures exhibit a larger back stress slope and increment. This indicates that heterogeneous materials, represented by gradient and layered structures, can accumulate more geometrically necessary dislocations than homogeneous structures, inducing more significant back stress strengthening, thus enabling heterogeneous materials to achieve an excellent strength-toughness match.
[0062] In addition, this application also provides applications of the aforementioned 15-5PH stainless steel, such as its use in aero-engine systems or aircraft structural components.
[0063] In some embodiments, the aforementioned 15-5PH stainless steel can be used for reinforcement and repair of components such as high-pressure compressor discs of engines and aviation fuel and hydraulic control systems.
[0064] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0065] Example 1
[0066] This embodiment provides a 15-5PH stainless steel with a heterogeneous layered structure, which is composed of alternating fine-grained and coarse-grained layers; both the fine-grained and coarse-grained layers contain BCC martensite and FCC austenite.
[0067] The preparation of this 15-5PH stainless steel includes: additive manufacturing of 15-5PH stainless steel spherical powder with a particle size of 15-53 μm using laser powder bed melting. The process parameters of the laser powder bed melting process are: laser power of 260W, scanning speed of 1200mm / s, scanning spacing of 0.06mm, powder thickness of 0.04mm, protective gas of high-purity argon, and forming substrate of stainless steel.
[0068] The scanning electron microscope image of the heterogeneous layered structure in the 15-5PH stainless steel is shown below. Figure 1 As shown, by Figure 1 It can be seen that the 15-5PH stainless steel prepared in this embodiment has a heterogeneous layered structure in the printing direction, consisting of alternating fine and coarse grain layers.
[0069] The backscattered electron diffraction pattern of the heterogeneous layered structure in the 15-5PH stainless steel is shown below. Figure 2 As shown, white represents FCC austenite, and the same applies below. The backscattered electron diffraction pattern of the fine-grained grains in the heterogeneous layered structure is shown below. Figure 3 As shown, the backscattered electron diffraction patterns of the fine-grained FCC austenite and BCC martensite layers in the heterogeneous layered structure are as follows: Figure 4 As shown, the backscattered electron diffraction pattern of the coarse-grained grains in the heterogeneous layered structure is as follows: Figure 5 As shown, the backscattered electron diffraction patterns of the coarse-grained FCC austenite and BCC martensite layers in the heterogeneous layered structure are as follows: Figure 6 As shown.
[0070] Depend on Figures 2 to 6 It can be seen that: the average grain size of the fine-grained layer is 1μm, and by volume percentage, FCC austenite accounts for 12% and BCC martensite accounts for 88%; the average grain size of the coarse-grained layer is 3μm, FCC austenite accounts for 6% and BCC martensite accounts for 94%.
[0071] The X-ray diffraction pattern of the printed 15-5PH stainless steel is as follows: Figure 7 As shown, by Figure 7 It can be seen that the microstructure of the 15-5PH stainless steel in the printed state consists of mostly α-martensite with BCC structure and a small amount of γ-austenite with FCC structure.
[0072] The printed room temperature tensile stress-strain curve of the 15-5PH stainless steel is shown below. Figure 8 As shown, by Figure 8It can be seen that the room temperature tensile strength, yield strength and elongation after fracture of the 15-5PH stainless steel in the printed state are 1161 MPa, 825 MPa and 17.5%, respectively.
[0073] The impact toughness of this 15-5PH stainless steel can reach 122.5 J / cm. 2 The scanning electron microscope image of the room temperature tensile fracture surface of the 15-5PH stainless steel in its printed state is shown below. Figure 9 As shown, the scanning electron microscope image of the room temperature impact fracture surface in the printed state is as follows. Figure 10 As shown. Combined with Figure 9 and Figure 10 It can be seen that the tensile and impact fracture surfaces of this 15-5PH stainless steel exhibit ductile fracture characteristics, with a large number of deep dimples.
[0074] Example 2
[0075] The difference between this embodiment and Embodiment 1 is that the process parameters of the laser powder bed melting process are: laser power of 300W, scanning speed of 1500mm / s, scanning spacing of 0.08mm, and powder thickness of 0.05mm.
[0076] Testing revealed that the 15-5PH stainless steel printed in this embodiment exhibited a heterogeneous layered structure in its microstructure. The fine-grained layer had an average grain size of 2 μm, with FCC austenite comprising 9% and BCC martensite comprising 91% by volume. The coarse-grained layer had an average grain size of 6 μm, with FCC austenite comprising 4% and BCC martensite comprising 96%. The room temperature tensile strength, yield strength, elongation after fracture, and impact toughness in the printed state were 1122 MPa, 742 MPa, 16.0%, and 103.0 J / cm², respectively. 2 .
[0077] Example 3
[0078] The difference between this embodiment and Embodiment 1 is that the process parameters of the laser powder bed melting process are: laser power of 280W, scanning speed of 1350mm / s, scanning spacing of 0.07mm, and powder thickness of 0.03mm.
[0079] Testing revealed that the 15-5PH stainless steel printed in this embodiment exhibited a heterogeneous layered structure in its microstructure. The fine-grained layer had an average grain size of 1.5 μm, with FCC austenite comprising 11% and BCC martensite comprising 89% by volume. The coarse-grained layer had an average grain size of 5 μm, with FCC austenite comprising 5% and BCC martensite comprising 95%. The room temperature tensile strength, yield strength, elongation after fracture, and impact toughness in the printed state were 1143 MPa, 796 MPa, 17.0%, and 114.3 J / cm², respectively. 2 .
[0080] Comparative Example 1
[0081] The difference between this comparative example and Example 1 is that the process parameters of the laser powder bed melting process are: laser power of 260W, scanning speed of 1800mm / s, scanning spacing of 0.08mm, and powder thickness of 0.03mm.
[0082] The scanning electron microscope image of the 15-5PH stainless steel without heterogeneous layered structure prepared in this comparative example is shown below. Figure 11 As shown, the scanning electron microscope image of the room temperature tensile fracture surface of the 15-5PH stainless steel in its printed state is as follows. Figure 12 As shown, the scanning electron microscope image of the room temperature impact fracture surface of the 15-5PH stainless steel in the printed state is as follows. Figure 13 As shown.
[0083] Combination Figure 8 as well as Figures 11 to 13 It can be seen that the microstructure of the 15-5PH stainless steel in the printed state prepared in this comparative example does not exhibit a heterogeneous layered structure. The room temperature tensile strength, yield strength, elongation after fracture, and impact toughness of this 15-5PH stainless steel in the printed state are 889 MPa, 598 MPa, 7.0%, and 17.4 J / cm², respectively. 2 The tensile and impact fracture surfaces of this 15-5PH stainless steel exhibit brittle fracture characteristics, with numerous cleavage steps and virtually no dimples.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that the process parameters of the laser powder bed melting process are: laser power of 350W, scanning speed of 1500mm / s, scanning spacing of 0.08mm, and powder thickness of 0.05mm.
[0086] Testing revealed that the microstructure of the 15-5PH stainless steel in the printed state prepared in this comparative example did not exhibit an heterogeneous layered structure. The room temperature tensile strength, yield strength, elongation after fracture, and impact toughness of this 15-5PH stainless steel in the printed state were 853 MPa, 583 MPa, 8.0%, and 19.7 J / cm², respectively. 2 .
[0087] Comparative Example 3
[0088] The difference between this comparative example and Example 1 is that the process parameters of the laser powder bed melting process are: laser power of 280W, scanning speed of 1200mm / s, scanning spacing of 0.10mm, and powder thickness of 0.04mm.
[0089] Testing revealed that the microstructure of the 15-5PH stainless steel in the printed state prepared in this comparative example did not exhibit an heterogeneous layered structure. The room temperature tensile strength, yield strength, elongation after fracture, and impact toughness of this 15-5PH stainless steel in the printed state were 872 MPa, 591 MPa, 8.5%, and 18.6 J / cm², respectively. 2 .
[0090] Furthermore, for ease of comparison, the room temperature tensile mechanical properties and impact toughness test results of Examples 1-3 and Comparative Examples 1-3 are summarized in Table 1.
[0091] Table 1 Performance Test Results
[0092]
[0093] As shown in Table 1, the 15-5PH stainless steel with heterogeneous layered structure prepared in Examples 1-3 has a room temperature tensile strength of 1122-1161 MPa, a yield strength of 742-825 MPa, an elongation after fracture of 16.0-17.5%, and an impact toughness of 103.0-122.5 J / cm². 2 Compared with the 15-5PH stainless steel without heterogeneous layered structure obtained in Comparative Examples 1-3, the tensile strength is increased by 26-36%, the yield strength is increased by 24-42%, the elongation after fracture is increased by 88-150%, and the impact toughness is increased by 423-604%.
[0094] In summary, this application creatively provides a method for preparing 15-5PH stainless steel that can achieve both strength and toughness. The resulting 15-5PH stainless steel has a specific heterogeneous layered structure, which can simultaneously possess superior strength and toughness. It is suitable for strengthening and repairing parts of aero-engine systems and aircraft structural components, such as high-pressure compressor discs of engines and aviation fuel and hydraulic control systems.
[0095] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A 15-5PH stainless steel, characterized in that, The microstructure of the 15-5PH stainless steel has a heterogeneous layered structure. The heterogeneous layered structure is composed of alternating fine-grained layers and coarse-grained layers; Both the fine-grained layer and the coarse-grained layer contain BCC martensite and FCC austenite, with the content of FCC austenite in the fine-grained layer being higher than that in the coarse-grained layer; The average grain size in the fine-grained layer is 1~2μm; by volume percentage, the proportion of FCC austenite in the fine-grained layer is 9~12%, with the remainder being BCC martensite; The average grain size in the coarse-grained layer is 3~6μm; by volume percentage, the coarse-grained layer contains 4~6% FCC austenite and the remainder is BCC martensite. The additive manufacturing method for 15-5PH stainless steel includes the following steps: additive manufacturing of 15-5PH stainless steel powder using laser powder bed melting; the process parameters for laser powder bed melting include: laser power of 260~300W, scanning speed of 1200~1500mm / s, scanning spacing of 0.06~0.08mm, and powder thickness of 0.03~0.05mm.
2. The 15-5PH stainless steel according to claim 1, characterized in that, The 15-5PH stainless steel has a tensile strength of 1122~1161 MPa, a yield strength of 742~825 MPa, an elongation after fracture of 16.0~17.5%, and an impact toughness of 103.0~122.5 J / cm. 2 .
3. An additive manufacturing method for 15-5PH stainless steel as described in claim 1 or 2, characterized in that, Includes the following steps: Additive manufacturing of 15-5PH stainless steel powder was carried out using laser powder bed melting. The process parameters for laser powder bed melting include: laser power of 260~300W, scanning speed of 1200~1500mm / s, scanning spacing of 0.06~0.08mm, and powder thickness of 0.03~0.05mm.
4. The additive manufacturing method according to claim 3, characterized in that, The 15-5PH stainless steel powder is a spherical powder with a particle size of 15-53 μm.
5. The application of 15-5PH stainless steel as described in claim 1 or 2 in aero-engine systems or aircraft structural components.
